THE PASSAGE TO OTHER WORLDS: FROM MORAL EDIFICATION TO COLLAPSE OF ALL VALUES - Tupan, Maria-Ana (International Journal of Research -GRANTHAALAYAH, 2021)
Is space relevant in a debate over the ethical dimension of a literary work? If we understand it as Foucault[1], Lefebvre[2], Soja[3] or Marc Auger[4] do, it is. In Andre Norton’s The Crossroads of Time[5], many worlds coexist as versions of an original earth, ruined by wars whose memories set agents under cover travelling across in order to defend what had remained of humanity besieged by monsters against a universal murderer, Kmoat Vo Pranj. The characters’ psychic powers depend on their interference with the environment – an idea probably originating with quantum experiments whose results depend on the interference of the measuring equipment with the system. An agent talks about alternative histories in an ecological version which relates individuals’ growth or success to favourable conditions in the world out there, to their or society’s benefit